Scenario Planning Approach for PT. ViewTron Indonesia in Developing it’s Business in Indonesia - Syukriadi, Loethano Novi; Sunitiyoso, Yos (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2021)
A market report says that the projectors’ business is growing promisingly over the next five years, globally. Asia Pacific market is a region that shows an increasing sales trend. In Indonesia, PT. ViewTron (the name is made vague due to confidentiality), an importing projectors company established in 2018, is growing significantly. However, due to the Covid-19 pandemic, the sales volume dropped drastically. The management is concerned about the future business of the company in Indonesia and what best strategies to deal with such future uncertainties. The scenario planning approach is selected to address the management’s concerns. A qualitative research methodology is used to analyze the situations that affect the company. A 2x2 matrix of scenario framework is developed reflecting critical uncertainties that might affect future business of PT ViewTron. The scenario shows the plausibility of future situations and offers strategy options for the company to manage the implications of each scenario. Before the occurrence of a scenario, the management should define early warning signals to alert the company on which scenario it is heading toward and what actions to take. By setting thorough scenario planning, the management could develop strategies that may envision future business uncertainties confidently.